Rancangan Evaluasi Vendor untuk Perusahaan Produksi Helmet dan Jasa Injection Molding - Olivia Harsono; I Nyoman Sutapa (Jurnal Titra, 2022)
Purchasing department is one of the most important departments because the company relies on the raw goods purchased by the purchasing department. The company also has suppliers or vendors of the raw products that the company needs. Vendor selection is an important task for every company, especially the purchasing department itself. Each vendor that has been selected requires a vendor evaluation to determine the assessment for each vendor that the company has used before. The vendor's assessment has several criteria that must be assessed in the vendor's assessment. Some of these criteria are the quality of the products they provide, the quantity or quantity of each item they send, the accuracy of the delivery by the vendor, the service provided by the vendor, and the last is the comparison of the price of the selected vendor with other vendors. The weighting assessment for each of these criteria was carried out using the AHP paired weighting method. The AHP method will be used to obtain a weighted value for each predetermined criterion. This weighting will later be used to assess each vendor in the company. The results of calculations using AHP state that these data are consistent and can be weighted.